Pedagogical-psychological and medical-biological problems of young judoists training system for competitions - Nohrin, M. Y. (The Russian Journal of Physical Education and Sport, 2016)
Annotation. An urgent task is to improve theoretical readiness of the whole coaching staff, to study physical and physiological bases of sports training, continuity in the work of trainers with their sportsmen. Materials. This scientific review describes the existing system of young judoists` modern training for important competitions and its urgent problems. First of all, it is the problem for a new division of young athletes into the age groups - under 18, under 23 and over 23. On the one hand, this division has some advantages, on the other hand, this division holds a young athlete from adulthood, not giving him an opportunity to take responsibility for making decisions, including sports decisions. We describe the most common mistakes that are made, mainly by coaches, while training young athletes, the ways to correct these mistakes and the ways out of the problems. The main difficulty stays the problem of weight loss, which is given special attention. Research methods: The work was held in terms of training junior judo team for a series of competitions, during which observation was held over the whole system of training functioning among young athletes, including the analysis of the coaching staff, sportsmen, a complex scientific group , medical - biological support. Results. The results of the research led to the fact that during the observation over a team of young athletes and their activity several groups of estimation criteria of the training system functioning of young judoists appeared, it concerns the following aspects: the absence of the system and the training plan in general, the trainers of national team and personal trainers don`t have common goals and objectives, the lack of basic knowledge of sports physiology among personal trainers of young athletes. Conclusion. The system of training young judoists for important competitions nowadays has several drawbacks, even in case of improvement and optimization methods introduction into it. However, it is impossible to create an ideal system of training, that is why, first of all, it is necessary to understand the existing system, study its organizational and juridical basis, study its weak points and all possible drawbacks, which can be eliminated and leveled, making situational corrections, gradually and systematically. Also it is necessary to reveal all strong points of the existing system of young judoists training and using its best qualities and features, gradually lead a young sportsman to victories at International competitions, making our country a leader.